Integrated Framework for Proper Constructability in Bridges Using Value Engineering and Analytical Network Process 'ANP" (Analytical Study): إطار متكامل لتحسين إنشائية الكباري باستخدام الهندسة القيمية وعملية الشبكة التحليلية "ANP" (دراسة تحليلية) - Nagwan El- Sayed Abo El- Enen, Khaled Mohamed Heiza, Ibrahim Mahmoud Mahdi (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
Due to recent environmental and Political requirements, and regulations of the construction industry, in which bridges is one of its important category, deciding its proper constructability is becoming vital. Therefor the objective of this research is to develop a decision model for selecting proper constructability of green bridges constructions, the model was built based on analytical network process (the ANP) soft were program, integrated with value engineering approach. For this analytical study different parameters are identified and ranked to be implemented for the decision model developed on the biases of four surveying studies conducted in this study the results of these surveying's was be analyzed by using the statically analytical program; "SPSS". Model validation and reliability is carried out using the analytical network process (ANP) for statistically analysis using case study which is a cable bridge project constructed in Egypt. ANP proves to be an effective framework for assessing readiness to adopt and facilitating TQM. The result of the study illustrate that the proper constructability alternative in green bridge concept for this determinate project is the concrete box girder type, upon this there is a cost loss of $3, 500 per square meter, equivalent to 50% losses, respect to the life cycle cost this is due to did not using the best alternate of the estimated project. upon the possibility of applying this decision model to such studies of infrastructure projects, and with respect to the results gained; it is recommend to apply the ANP model with respect to VE procedures to bridges projects of all kinds and their determinants, as well as all other construction projects, especially national ones, in future studies, which allows decision- makers to make decisions that aim at the highest quality without any waste in unnecessary costs.
Keywords: Analytic Network Process (ANP); الشبكة التحليلية (ANP); Weighted Graph; رسم بياني مرجح; Value Management (VM); إدارة القيمة; Value Engineering (VE); Un Weighted Matrix; مصفوفة مرجحة; limit matrix; مصفوفة الحد; Weighted Matrix